A brave new world of knowledge : Shakespeare's The tempest and early modern epistemology - Sokol, B. J. (Fairleigh Dickinson University Press ; Associated University Presses, 2003)
"A Brave New World of Knowledge studies Shakespeare's The Tempest using materials relating to the history of early seventeenth-century proto-science. These materials are either newly investigated, or are derived from sophisticated recent work that has been little consulted before by Shakespeare scholars." "This book is centrally concerned with a classic of dramatic literature which is extraordinary in terms of its genre, structure, style, language, mythos, characterization, and long-term influence. All of these elements are addressed. Yet, to do so, the book finds it valuable to confront quite large questions about the nature and dissemination of the early seventeenth-century so-called "scientific revolution."" "The study also considers, somewhat generally at its outset and then in varied specific ways throughout, what the best interdisciplinary approach to a Shakespeare play might be. It argues for the futility, or possible deceptiveness, of any search for a "master discourse" which could provide a single main correlative for understanding The Tempest. Instead it illustrates, and argues for the superiority of, interdisciplinary approaches to the complex play which are empirically led and so never irrefutable, and which consciously intend to build on a body of earlier work so as to achieve accumulative increments of understanding. These would therefore be approaches that observe both the established findings and the disciplinary norms of all of the interdisciplinary areas in question." "The main part of this book is concerned with the location of a surprising range of examples of reflections in The Tempest of specific new breakthroughs of knowledge, or new challenges to knowledge, in fields as diverse as natural history, meteorology, ethnology, scientific instrumentation, and time measurement. Explorations of the historical and intellectual contexts of such instances of knowledge acquisition, and explorations of how these instances and contexts vitally connect with the play, must count as the most valuable contributions of this book."--BOOK JACKET.